2021
DOI: 10.1590/1414-431x202010037
|View full text |Cite
|
Sign up to set email alerts
|

Is birth weight associated with pregestational maternal BMI? BRISA Cohort, Ribeirão Preto, Brazil

Abstract: Given the increase of women with excess weight or obesity and its possible effects on birth weight, the present study aimed to investigate the association between pregestational maternal body mass index (BMI) and birth weight in a birth cohort from Ribeirão Preto, SP, Brazil. This was a prospective study conducted on 1362 mother-child pairs involving singleton births. The women were evaluated using standardized questionnaires during the second trimester of pregnancy and at the time of childbirth. Information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(43 reference statements)
0
2
0
2
Order By: Relevance
“…Some authors also believe that factors such as the weight and height of the mother before pregnancy and the weight gain of the pregnant woman are strongly related to birth weight. (Trombe et al, 2020) Birth weight is the weight of a baby measured during the first 24 hours after birth. The higher the birth weight, the higher the risk of tearing the perineum.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors also believe that factors such as the weight and height of the mother before pregnancy and the weight gain of the pregnant woman are strongly related to birth weight. (Trombe et al, 2020) Birth weight is the weight of a baby measured during the first 24 hours after birth. The higher the birth weight, the higher the risk of tearing the perineum.…”
Section: Resultsmentioning
confidence: 99%
“…Os artigos analisados na revisão apresentam diversos problemas associados a obesidade na gestação, que podem acarretar em problemas na vida da mãe e do neonato, dentre elas é possível destacar na mãe a presença de diabetes mellitus gestacional, hipertensão, maior prevalência de cesarianas, hemorragia pós-parto, suscetibilidade para o aborto, infecções urinárias, aumento da mortalidade entre outros. Para o filho os mais presentes foram: macrossomia fetal, fetos pequenos para idade gestacional (PIG) ou grandes para idade gestacional (GIG), prematuridade, hiperinsulinemia e resistência à insulina, aumento da mortalidade fetal e comorbidades na infância, além de distúrbios metabólicos e respiratórios, entre outros (Nascimento et al, 2018a;Ferreira et al, 2019;Lana et al, 2020;Oliveira et al, 2020;Paulino et al, 2020;Silveira et al, 2021;Teles, 2021;Trombe et al, 2021).…”
Section: Fonte: Autoria Própria (2022)unclassified
“…Um estudo de corte transversal realizado com puérperas internadas na Maternidade Darcy Vargas (Joinville-Santa Catarina), entre os meses de maio e junho de 2013, apontou que a dicotomia obesidade e gestação traz repercussões negativas para a mãe, como a prevalência de cesarianas e hemorragias de grande porte (Silva et al, 2014). Corroborando com os achados de Lana et al (2020), Paulino et al (2020), Trombe et al (2021. Outro estudo, realizado em um hospital no Paraná, em 2017, mostrou que as cesarianas ocorreram devido a uma combinação de fatores em decorrência de comorbidades durante o período gravídico (Carreli et al, 2020).…”
Section: Fonte: Autoria Própria (2022)unclassified
“…Fetal with large for gestational age and macrosomia were strongly associated with maternal obesity and it was the single most powerful indicator of shoulder dystocia. [48][49][50] A recent study among obese Polish women found that the adjusted risk of macrosomia was more than three folds. 51 The prevalence of postdate, MSAF and resuscitation requirements among macrosomic babies were also higher.…”
Section: Fetal and Neonatal Complicationsmentioning
confidence: 99%